2019
DOI: 10.1093/advances/nmy123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns and Birth Outcomes: A Systematic Review and Meta-Analysis

Abstract: Findings on the relations of maternal dietary patterns during pregnancy and risk of preterm birth and offspring birth size remain inconclusive. We aimed to systematically review and quantify these associations. We searched MEDLINE, Embase, CENTRAL, and CINAHL up to December 2017. Three authors independently conducted a literature search, study selection, data extraction, and quality assessment. Summary effect sizes were calculated with random effects models and studies were summarized narratively if results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 80 publications
11
129
4
3
Order By: Relevance
“…It is widely believed that maternal diet is associated with progeny's body weight gain and obesity. 33,34 However, the effects of sucralose on the weight gain were not fully consistent in previous studies. Abou-Donia reported that administration of sucralose approximately 1.1 to 11 mg/kg BW/day from the 4th week after birth for 12 weeks significantly increased body weight in rats.…”
Section: Discussionmentioning
confidence: 57%
“…It is widely believed that maternal diet is associated with progeny's body weight gain and obesity. 33,34 However, the effects of sucralose on the weight gain were not fully consistent in previous studies. Abou-Donia reported that administration of sucralose approximately 1.1 to 11 mg/kg BW/day from the 4th week after birth for 12 weeks significantly increased body weight in rats.…”
Section: Discussionmentioning
confidence: 57%
“…As suggested by National Institute of Nutrition (NIN), India, the energy demand in pregnancy increases by 350 kcal along with increased demand of macronutrients and micronutrients [15]. However, studies pertaining to dietary intake throughout gestation in Indian women are insufficient and those available were mostly cross-sectional in nature [16]. Owing to the fact that dietary behaviour has many implications on mother and child's weight, this prospective cohort study was conducted to evaluate GWG and nutrient intake in all trimesters of pregnancy and investigate the relationship between themselves along with that of BW.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other prenatal factors remain to be studied. Indeed, healthy dietary patterns during pregnancy have been shown to be positively associated with birth weight (Chia et al, 2019;Emmett, Jones, & Northstone, 2015), whereas negative associations were observed between both unhealthy dietary patterns and maternal depression and birth weight (Chia et al, 2019;Field, 2011). One review also reported a birth length decrease in offspring of mothers with depression during pregnancy (Field, 2011).…”
Section: Introductionmentioning
confidence: 99%